If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 = 3(2p + -6) Reorder the terms: 28 = 3(-6 + 2p) 28 = (-6 * 3 + 2p * 3) 28 = (-18 + 6p) Solving 28 = -18 + 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. 28 + -6p = -18 + 6p + -6p Combine like terms: 6p + -6p = 0 28 + -6p = -18 + 0 28 + -6p = -18 Add '-28' to each side of the equation. 28 + -28 + -6p = -18 + -28 Combine like terms: 28 + -28 = 0 0 + -6p = -18 + -28 -6p = -18 + -28 Combine like terms: -18 + -28 = -46 -6p = -46 Divide each side by '-6'. p = 7.666666667 Simplifying p = 7.666666667
| 7h(11h-8)= | | 3x(2x+20)=180 | | Y=4(-3x-3) | | 18x^6*(12x^2-24x)=0 | | Y=10x-4-6x+12 | | -2t+8=-t | | 18x^6*12x^2-24x=0 | | Y=5(3x-2) | | Y=8x+7+5x+3 | | 5x+4(2x+3)=x | | -10-2r=10+8r+10 | | (X^2+26x-39)=0 | | 5-7/2x | | A+B=74 | | 46+9x=146-3x | | 18-6n=3(2-n) | | f(x)=x-x-12 | | 3y-6=36 | | lnx+lnx^6=14 | | Y=-6/5x-3/5 | | 12x+10y=-6 | | (9/2)(-33/10) | | -2-2m=-9-m | | 10(1a+3b)=-20 | | -6+7q=5q | | x+3=2x+1-x+2 | | 8. 4m+5n=25 | | 3(2x+4)=-2(4x-13) | | 4x^3-3x=13 | | -8y-9=-10y+9 | | -3/2=-2/5y-5/3 | | 1-2x+3=2x+8 |